Biogeography and comparative cytogenetics between two populations of Hoplias malabaricus (Bloch, 1794) (Ostariophysi: Erythrinidae) from coastal basins in the State of Bahia, Brazil - Jacobina, Uedson Pereira; Affonso, Paulo Roberto Antunes de Mello; Carneiro, Paulo Luiz Souza; Dergam, Jorge Abdala (Neotropical Ichthyology, 2009)
The species Hoplias malabaricus is a predator fish found in nearly all cis-Andean basins. From a cytogenetic point of view, this species comprises, at least, seven differentiated karyomorphs. Several localities have been formerly analyzed in Brazil, however, some regions, such as Bahia State, remain underrepresented. Recently, the Brazilian Environment Ministry classified both Itapicuru and Contas river basins (entirely located within Bahia territory) as priority conservation areas, whose biodiversity status lacks enough information. Therefore, the goal of the present work was to characterize, cytogenetically, populations of H. malabaricus from both basins, by using conventional staining, Ag-NOR and C-banding techniques. All specimens presented a diploid number of 2n = 40 with metacentric/submetacentric chromosomes, without differences between sexes, thereby representing the so-called "karyomorph F". The first metacentric pair presented a remarkably larger size in relation to the other pairs. The NORs were multiple, comprising the terminal region on long arms of two chromosomal pairs in both populations. However, the C-banding pattern was somewhat distinguishable between samples. Although sharing heterochromatic blocks at centromeric region of all chromosomes, the population from Itapicuru River basin appeared to have some more conspicuous blocks than those observed in the population from Contas River basin. The similar karyotype observed in both populations suggests a common geological history between them. The present results represent an advance in the knowledge about the cytogenetic pattern of H. malabaricus populations from poorly studied basins.

A espécie Hoplias malabaricus é um predador que ocorre em praticamente todas as bacias cis-andinas. Sob o ponto de vista citogenético, ela compreende, pelo menos, sete cariomorfos diferenciáveis. Várias localidades já foram previamente analisadas no Brasil, porém, algumas regiões, como o Estado da Bahia, permanecem pouco amostradas. Recentemente, o Ministério de Meio Ambiente classificou as bacias do rio Itapicuru e Contas (inteiramente localizadas na Bahia), como áreas prioritárias de conservação, cuja biodiversidade carece de informações suficientes. Neste sentido, o objetivo do presente trabalho foi caracterizar citogeneticamente populações de H. malabaricus nessas bacias, por meio de técnicas de coloração convencional, Ag-RON e bandamento C. Todos os espécimes e populações analisadas apresentaram número diploide 2n = 40 com cromossomos metacêntricos/submetacêntricos, sem diferenças entre os sexos, representando assim o denominado "cariomorfo F". O primeiro par metacêntrico apresentou tamanho notavelmente maior que os demais pares. As RONs foram múltiplas, ocupando a região terminal do braço longo de dois pares cromossômicos em ambas populações. Entretanto, os padrões de heterocromatina foram relativamente diferenciáveis entre as bacias hidrográficas estudadas. Apesar de compartilharem blocos heterocromáticos na região centromérica de todos os cromossomos, a população da bacia do Itapicuru apresentou alguns blocos mais conspícuos em relação aos da bacia do rio de Contas. O cariótipo similar encontrado em ambas as populações parece indicar uma história geológica em comum. Os dados obtidos representam um avanço no conhecimento dos padrões citogenéticos de populações de H. malabaricus provenientes de bacias pouco estudadas.
Keywords: Fish; Karyomorphs; Brazilian coastal rivers; Geographic distribution